Patient-Reported Outcome Measures in Clinical High Risk for Psychosis: A Systematic Review. Issue 1 (23rd February 2023) - Addington, Jean; Chao, Amanda; Braun, Amy; Miller, Madeline; Farris, Megan S
Abstract: A key issue in both research and clinical work with youth at clinical high risk (CHR) of psychosis is that there are clearly heterogenous clinical outcomes in addition to the development of psychosis. Thus, it is important to capture the psychopathologic outcomes of the CHR group and develop a core outcomes assessment set that may help in dissecting the heterogeneity and aid progress toward new treatments. In assessing psychopathology and often poor social and role functioning, we may be missing the important perspectives of the CHR individuals themselves. It is important to consider the perspectives of youth at CHR by using patient-reported outcome measures (PROMs). This systematic review of PROMs in CHR was conducted based on a comprehensive search of several databases and followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Sixty-four publications were included in the review examining PROMs for symptoms, functioning, quality of life, self-perceptions, stress, and resilience. Typically, PROMs were not the primary focus of the studies reviewed. The PROMs summarized here fit with results published elsewhere in the literature based on interviewer measures. However, very few of the measures used were validated for CHR or for youth. There are several recommendations for determining a core set of PROMs for use with CHR.